Chironomus sancticaroli (Diptera, Chironomidae) as a Sensitive Tropical Test Species in Laboratory Bioassays Evaluating Metals (Copper and Cadmium) and Field Testing - Dornfeld, Carolina Buso [UNESP]; Rodgher, Suzelei [UNESP]; Negri, Rogério Galante [UNESP]; Espíndola, Evaldo Luiz Gaeta; Daam, Michiel A. (Springer Nature, 2019)
Despite that chironomids are the most widely used benthic insect test species worldwide, little research has been conducted so far with tropical chironomid representatives. This study was designed to evaluate the indigenous midge Chironomus sancticaroli as a candidate test species for use in tropical toxicity assessments. To this end, laboratory water-only toxicity tests were conducted evaluating copper and cadmium. Obtained lethal concentration values were overall comparable or lower than those reported for other chironomids, including those most commonly used in temperate regions (C. riparius and C. dilutus). In addition, C. sancticaroli was deployed in situ in the Monjolinho River (São Paulo State, Brazil), and toxicity of sediment from this river was evaluated in the laboratory. Several field water and sediment quality parameters also were measured to enable correlating these with the effects observed in these toxicity tests. Field sediment toxicity to C. sancticaroli appeared to be related with sediment endosulfan concentrations, whereas effects noted in the in situ test were likely due to low pH values measured in river water. Chironomus sancticaroli appears to be a suitable candidate for inclusion as a test species in tropical toxicity evaluations in both the laboratory and the field.